Implementasi Reward Dan Punishment Di Pondok Pesantren Kalimantan Timur - Fuad, Misbahul (Jurnal Tarbiyah dan Ilmu Keguruan Borneo, 2023)
Reward and Punishment is a very important element of management in education. Likewise, Islamic Education. The author will examine these two things in two Islamic boarding schools in East Kalimantan, namely Ibadurrahman in Tenggarong and Al- Mujahidin in Samarinda. This research will use field data with interview, documentation, and observation techniques. The validity of the data will be triangled over the data that has been obtained. The results of this study reveal that the process of granting rewards and punishments in the modern Islamic boarding school Ibadurrahman in giving punishment to students through several processes, starting from the warning in place, called to care until given punishment by the caregivers. The implementation of the punishment has its own officer. While in the Al Mujahidin Islamic boarding school in giving punishment to students starting from the warning, the summons to the security office until given the punishment while the process of providing direct punishment carried out in security based on the specified time.